Classical global solutions for compressible radiative flow in a slab under semi-reflexive boundary conditions. (October 2017) - de Azevedo, F.S.; Sauter, E.; Thompson, M.
Abstract: Classical global solutions are established for a model of compressible radiative flow in a slab under semi-reflexive boundary conditions using energy–entropy estimates and a homotopic version of the Leray–Schauder fixed point Theorem together with classical Friedman–Schauder estimates for linear second order parabolic equations in boundary Hölder spaces. Highlights: Existence was established for radiative–conductive problem coupled with motion. The theory of existence is based on a homotopic Leray–Schauder fixed point Theorem. The theory of existence was established in classical functional spaces.